IMPLEMENTATION OF SPACE GEOMETRY LEARNING USING GEOGEBRA TO IMPROVE PROBLEM SOLVING SKILLS - Pamungkas, Megita Dwi; Nugroho, Heny (MaPan : Jurnal Matematika dan Pembelajaran, 2020)
Prospective mathematics teachers must be equipped with problem solving skills because it has a very important place in the mathematics curriculum. The purpose of this research is to get an overview of improving the problem solving skills of prospective mathematics teachers by implementing GeoGebra on space geometry learning. The research was conducted in Study Program of Mathematics Education, Tidar University in the second semester students. This research uses quasi-experimental method, with nonequivalent control group pretest-posttest design using two groups, namely experimental group consisting of 36 students got GeoGebra-based space geometry learning and control group consisting of 35 students got conventional space geometry learning. Research instruments in the form of observation sheets and test instruments in the form of pretest and posttest to measure achievements of problem solving skills improvement. The data obtained is then processed and analyzed by calculating the percentage of learning implementation and calculating the average normalized gain score (N-Gain). The results showed that GeoGebra-based Space Geometry learning can improve problem solving skills. In the experimental group, problem solving skills were improved in high category, while in the control group the improvement of problem solving skills in moderate category.